Evaluation of leptin hormone and Tumor necrosis factor levels in patients with type two diabetes mellites - Qaiser I. Mahdi,; Mahdi M. Thuwaini,; Hamid J. Abbas, (University of Thi-Qar Journal of Science, 2023)
: Type 2 diabetes mellitus (T2DM) is a leading cause of mortality and morbidity worldwide. Leptin, an adipokine with the primary function of regulating energy balance, is found to mediate insulin secretion and sensitivity in peripheral tissues. Aims: Hence, we aimed to determine the role of leptin in the development of insulin resistance (IR) in newly diagnosed T2DM patients and determine tumor necrosis factoralpha (TNF-α). Materials and methods: A case control study a total of 80 patients and 50 control groups, used Cobas E311 device to measure glucose, whereas HbA1c used D-10 hemoglobin Hba1c device whereas other parameters used ELISA methods were used to analyses 130 samples Results: Highly significant increase level of  Fasting blood sugar, hemoglobin A1c, Insulin, Leptin and HOMA- insulin resistance whereas   significant decrease level of TNF alpha and , Plasminogen activator inhibitors -1 in patient type two diabetes mellitus compared to the control group. Conclusion: increased the level of leptin levels while TNF-α levels were decreased in type 2 diabetes patients.